2007
DOI: 10.1002/cbic.200700006
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Protocol for Solution Structure Determination of Copper(II) Proteins: the Case of CuIIZnII Superoxide Dismutase

Abstract: We have developed an optimized protocol to solve the solution structure of copper(II) proteins. After assignment, proton-proton NOEs are used for the shell where 1H spectra are conveniently observed. In a shell closer to the metal ion, 13C NMR spectra with band-selective homonuclear decoupling provide the assignment of all nuclei except for those of the metal ligands. A convenient method for the measurement of 13C longitudinal-relaxation rates (R1) of carbonyls and carboxylate moieties is proposed. 1H NOEs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…[1][2][3] Amongt hem, the copper(II)-zinc(II) SOD is present in the plasma and in extracellular spaces, and it decomposess uperoxider adicals into molecular oxygen and hydrogen peroxide. [4][5][6] The latter molecules are subsequently removed by the catalase enzyme. [7] However,s upplementation of SOD is difficult owing to its high sensitivity to environmentalc onditions (e.g.,t emperature, pH, and complex nature in biofluids).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Amongt hem, the copper(II)-zinc(II) SOD is present in the plasma and in extracellular spaces, and it decomposess uperoxider adicals into molecular oxygen and hydrogen peroxide. [4][5][6] The latter molecules are subsequently removed by the catalase enzyme. [7] However,s upplementation of SOD is difficult owing to its high sensitivity to environmentalc onditions (e.g.,t emperature, pH, and complex nature in biofluids).…”
Section: Introductionmentioning
confidence: 99%
“…In addition there were 25 1 H-15 N cross-peaks observable in the diamagnetic but not paramagnetic form. In these cases, it was assumed that this was due to broadening of the 1 H resonances beyond detection, and an upper distance limit to the Cu ion of 10 Å was used, without lower limit (39). The remaining residues corresponded to peaks for which accurate PRE determination was not possible.…”
mentioning
confidence: 99%
“…After 6 days the cells were harvested by centrifugation. The NP2 protein was isolated and purified as described elsewhere, 39 but included the addition of hemin during the purification to complex any apo-NP2 that might be present (0.2 mL of ~2 mM hemin dissolved in a few drops of DMSO and diluted into pH 7.5 sodium phosphate buffer). A preliminary 1 H, 15 N-HSQC spectrum, recorded at pH 5.0 and 298 K, showed that there were only three amide 1 H, 15 N cross peaks in the normal protein amide window (5.5 – 11.0 ppm 1 H, 110 – 140 ppm 15 N) even down to the noise floor, and one additional amide cross peak, at 2.90 1 H, 116.0 15 N ppm, which confirmed that there was no measurable scrambling of the 15 N (and by implication, the 13 C) label.…”
Section: Methodsmentioning
confidence: 99%